Early Pleistocene climate-induced erosion of the Alaska Range formed the Nenana Gravel - Sortor, Rachel N.; Goehring, Brent M.; Bemis, Sean P.; Ruleman, Chester A.; Caffee, Marc W.; Ward, Dylan J. (Geology, 2021)
The Pliocene-Pleistocene transition resulted in extensive global cooling and glaciation, but isolating this climate signal within erosion and exhumation responses in tectonically active regimes can be difficult. The Nenana Gravel is a foreland basin deposit in the northern foothills of the Alaska Range (USA) that has long been linked to unroofing of the Alaska Range starting ca. 6 Ma. Using Al-26/Be-10 cosmogenic nuclide burial dating, we determined the timing of deposition of the Nenana Gravel and an overlying remnant of the first glacial advance into the northern foothills. Our results indicate that initial deposition of the Nenana Gravel occurred at the onset of the Pleistocene ca. 2.34 Ma and continued until at least ca. 1.7 Ma. The timing of initial deposition is correlative with expansion of the Cordilleran ice sheet, suggesting that the deposit formed due to increased glacial erosion in the Alaska Range. Abandonment of Nenana Gravel deposition occurred prior to the first glaciation extending into the northern foothills. This glaciation was hypothesized to have occurred ca. 1.5 Ma, but we found that it occurred ca. 0.39 Ma. A Pleistocene age for the Nenana Gravel and marine oxygen isotope stage 10 age for the oldest glaciation of the foothills necessitate reanalysis of incision and tectonic rates in the northern foothills of the Alaska Range, in addition to a shift in perspective on how these deposits fit into the climatic and tectonic history of the region. Geological Society of America Graduate Student Research Grant; Tulane University Lavin Bernick Faculty Grant Published version We thank Denny Capps, Mike Frothingham, Keir Nichols, and Chandler Powers for assistance with sample collection. We thank Adrian Bender, Julie Brigham-Grette, Mike Taylor and one anonymous reviewer for their thoughtful insight, which greatly improved the manuscript. Field work travel was funded in part by a Geological Society of America Graduate Student Research Grant. We thank the staff of PRIME Lab (Purdue University, ...